A novel compound heterozygous COL4A4 mutation in a Chinese family with Alport syndrome: A care case report. Issue 47 (24th November 2021) - Chen, Ji-Yu; Cui, Jing-Jing; Yang, Xi-Ran; Li, Yan-Fang; Zhang, Yan-Hua; Chen, Jia-Ni; Lin, Jun-Yu; Zhao, Bo
Abstract: Rationale: Alport syndrome (AS) is an inherited progressive renal failure, characterized by kidney disease, hearing loss, and eye abnormalities. Patient concerns: A 7-year-old male child was admitted for persistent microscopic hematuria and proteinuria. Diagnoses: Combined with clinical manifestations, laboratory testing, pathological changes of kidney and sequencing results, the patient was diagnosed as AS. Interventions: The patient was treated with ACEI and tacrolimus drugs for 2 years, but continued to have hematuria and proteinuria. Thus, a genetic analysis was performed using next-generation sequencing in four affected members from the family. Outcomes: The findings revealed triple compound heterozygous mutation of COL4A4 : three novel variations, c.1045C>T (p. R349X), c.3505+1G>A (splicing), and c.2165G>A (p. G722D). Lessons: This study was novel in finding that a triple variant of the COL4A4 gene simultaneously in trans and in cis. The effects of multiple mutation sites and the type of gene mutation in AS were also underlined.